Preterm labor and associated factors. - Saha, Rachana (2000)
ABSTRACT: This study was conducted in the maternity hospital, Thapathali in the year 2000. Objective: The overall objective of the study was to see two factors associated with preterm labor and delivery like UTI and immediate previous pregnancy outcome such as previous abortion and previous preterm delivery. Methodology: A prospective hospital based cross-sectional study was carried out in 100 patient of preterm labor and delivery which formed the study group and hundred patient of term labor and delivery which formed the comparative group. UTI was defined for the purpose of the study by patients symptoms, signs and urine examination reports which included pus cells, proteinuria and culture. At the time of admission patients of study and comparative group were asked about complaints of urinary tract infection and about immediate previous pregnancy outcome. Mid-stream urine was collected for the purpose of urine examination. Patients were treated according to sensitivity reports. Results: incidence of preterm delivery during the study period was 3.6%. UTI was present in 31% cases of study group and 9% in comparative group. P-value was 0.00073, highly significant. In both groups UTI was more prevalent in age group of 25-29 and in multigravida. Inspite of adequate antenatal care 25% of cases in study group had UTI in study group was at 28-29 weeks of gestation. Pus cells>-_5 showed significant correlation with urine culture and proteinuria showed poor correlation. E. Coli was the commonest organism isolated in both groups. Cephalexin was most prescribed drug and Gentamycin was the most sensitive drug. 27% of multi gravid had history of previous preterm delivery with 95% C.I (13-44). 13% of multigravida had history of previous mid trimester abortion with 95 C.I (4-28). 5% of multigravida had history of previous induced abortion with 95 C.I (2-18). Conclusion: Present study shows significant association of UTI with preterm labor and also significantly correlates with history of previous abortion and preterm delivery.